Qualitative Estimation For Northern and Southern Kufa Drainage Water of Najaf - Luay Q .Hashem; Fadel S. Guhe; Azzam H. Al-Hadithy; Alham A. Hasson (Journal of Madenat Alelem University College, 2016)
The project aims to develop a database for the quantity and quality water of northern and southern Kufa drainage system, Project included collection of 8 samples every month for one year which was divided in four season each of them contain average of three months, the samples were taken along two Kufa drainages water. The data indicated the electric conductivity Ec of two kufa drainage water during spring season was few value compared others seasons due to dilute rainwater, while increasing of electric conductivity during summer season was due to drainages proceeding and increased evaporation of heat temperatures during summer season, winter and autumn seasons were noted slight decreasing of Ec was due to evaporation decreasing with high level of drainage water and limitation of drainage process agricultural land. In addition result indicated high salinity in southern drainage water and it was moderate salinity according of classification system of USA salinity lab because there are treatment station named barakia drain its pollutant